Perancangan user interface pada game edukasi bahasa arab menggunakan metode design thinking - Fajri Fahreza Azeta; Nazruddin Safaat H; Muhammad Irsyad; Febi Yanto (Computer Science and Information Technology, 2023)
Technology is developing rapidly, providing convenient access to information, and sparking interest in technological developments. The growth of technology influences children's learning. The integration of technology creates new and exciting learning experiences, especially in early childhood education. The use of smartphones as innovative learning media offers interactivity and attraction. In game development, attention to the User Interface (UI) is crucial to ensure a suitable gaming experience that supports the overall game experience. The research methodology used in conducting this research is the "Design Thinking" method, this method uses a process of combining designer thinking and techniques to meet the need to find a way out and look for alternative solutions. Sampling was carried out deliberately from respondents who had criteria that were in accordance with the research. The samples used in this research were children who were introduced to Arabic. After asking questions from respondents consisting of 16 people from general public backgrounds, students and university students representing the results of the System Usability Scale calculation, there were interpretation results of the average SUS Score, namely 76.09375. So the User Interface design prototype of "Arabic Educational Game" is included in the Good scale. Based on the results of the research, it is concluded that the User Interface has completed the design of the Design Thinking method with the Arabic Educational game to make it more interesting and easier to use, so that it can meet needs and provide interesting gaming experience for users.